2020
DOI: 10.1002/jts.22542
|View full text |Cite
|
Sign up to set email alerts
|

Social Support Moderates the Association Between Posttraumatic Stress Disorder Treatment Duration and Treatment Outcomes in Telemedicine‐Based Treatment Among Rural Veterans

Abstract: For patients participating in trauma‐focused psychotherapies for posttraumatic stress disorder (PTSD), such as cognitive processing therapy (CPT), pretreatment characteristics may moderate treatment effectiveness. For instance, preexisting supportive relationships may encourage skill utilization or provide contrasts to maladaptive cognitive biases highlighted in trauma‐focused treatments for PTSD. Such pretreatment characteristics are important to study in rural individuals, who may experience barriers to init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 59 publications
1
15
1
Order By: Relevance
“…They are especially important during and after traumatic stress exposures [ 24 , 100 ], with evidence suggesting that they predict recovery in collective/community trauma settings (a traumatic event[s] such as a pandemic or natural disaster that affects an entire people group or society; [see 28, 80, 81]), and are integrally associated with PTSD symptoms over time [ 101 ]. In clinical settings, social support influences patients’ ability to extract benefits from trauma-focused treatments [ 12 , 45 , 58 , 76 ]. Cross-sectional research conducted during the COVID-19 pandemic identified social support as a predictor and buffer of mental health among healthcare workers [ 31 ] and community members [ 43 ], and likely to be involved in development, persistence, and/or resolution of post-pandemic PTSD [ 104 ].…”
Section: Resilience Via the Interplay Of Interpersonal And Intra-indi...mentioning
confidence: 99%
“…They are especially important during and after traumatic stress exposures [ 24 , 100 ], with evidence suggesting that they predict recovery in collective/community trauma settings (a traumatic event[s] such as a pandemic or natural disaster that affects an entire people group or society; [see 28, 80, 81]), and are integrally associated with PTSD symptoms over time [ 101 ]. In clinical settings, social support influences patients’ ability to extract benefits from trauma-focused treatments [ 12 , 45 , 58 , 76 ]. Cross-sectional research conducted during the COVID-19 pandemic identified social support as a predictor and buffer of mental health among healthcare workers [ 31 ] and community members [ 43 ], and likely to be involved in development, persistence, and/or resolution of post-pandemic PTSD [ 104 ].…”
Section: Resilience Via the Interplay Of Interpersonal And Intra-indi...mentioning
confidence: 99%
“…Jain et al, 2020;Weiss, Azevedo, Webb, Gimeno, & Cloitre, 2018). Recent studies of trauma-focused treatments have found that a significant mediator and moderator of PTSD outcome has been social support where social support at the beginning of treatment as well as during the course of treatment was associated with PTSD symptom reduction (Campbell, Erbes, Grubbs, & Fortney, 2020;Price et al, 2018). These observations have led to a growing interest in the contributions that positive social and interpersonal experiences can make to PTSD recovery (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Withdrawal from social interaction was a second prevalent theme; interviewees reported behaving in ways that both actively and passively severed their connections with others. By extension, clinical interventions for soul wounds should consider involving both peer leaders and family members in treatment, particularly given evidence that social support can boost the effectiveness of programming for military personnel (e.g., Campbell et al, 2020; Meis et al, 2019; Whybrow et al, 2015). A third overarching theme concerned the stigma of suffering, whereby people with soul wounds judged themselves as weak and wondered if others would judge them poorly as well.…”
Section: Discussionmentioning
confidence: 99%